Complex thermokinetic characterization of polydioxanone for medical applications: Conditions for material processing - Svoboda, Roman; Machotová, Jana; Krbal, Miloš; Jezbera, Daniel; Nalezinkova, Martina; Loskot, Jan; Bezrouk, Ales (Elsevier Science, 2023)
Polydioxanone is used in numerous medical applications, e.g., biodegradable sutures and implants, for its excellent biocompatibility and appropriate degradation time. However, detailed knowledge of the polydioxanone thermokinetic behavior is essential to achieve the required properties of the particular medical appliance produced. Differential scanning calorimetry (DSC) was used for thermokinetic characterization of polydioxanone. The study was focused on three phenomena associated with the amorphous/semi-crystalline state: structural relaxation, cold crystallization, and thermal degradation. The glass transition kinetics was described in terms of the Tool-Narayanaswamy-Moynihan model with the following parameters: Delta h* = 679 kJ mol(-1), log(A/s) = 311.76, beta = 0.50, x = 0.45. The increasing degree of crystalline phase in the polymeric matrix led for the relaxation movements to a gradually decreasing dependence on structural arrangement. The cold crystallization of polydioxanone was described in terms of the autocatalytic Sestak-Berggren model with the following parameters: E = 95.2 kJ mol(-1), log(A/s(-1)) = 15.04, M-AC = 0.79, N-AC = 0.70. The highest achieved amounts of crystalline phase differed between 53 and 63% depending on the route to the crystal formation (either the crystal growth from the melt during slow cooling or the growth from the fully amorphous phase during slow heating). The kinetic predictions based on the non-isothermal and isothermal crystallization data were found to be in good agreement. Thermal decomposition of polydioxanone starts at 190 degrees C via depolymerization to p-dioxanone monomer and consequent evaporation. However, the polydioxanone starts to partially depolymerize already at 150 degrees C, shortening its chains and decreasing average molecular weight. Based on the present thermokinetic characterization, the optimum processing conditions for polydioxanone production by means of hot melt extrusion and molding were discussed.
Komplexní termokinetická charakterizace polydioxanonu pro medicínské aplikace: podmínky zpracování materiálu
Keywords: Polydioxanone; DSC; Crystal growth; Structural relaxation; Thermal degradation; Depolymerization; polydioxanon; DSC; růst krystalů; strukturní relaxace; tepelná degradace; depolymerizace